Effect of Emitted Wavelength and Light Guide Type on Irradiance Discrepancies in Hand-Held Dental Curing Radiometers - Atsushi Kameyama; Akiko Haruyama; Masako Asami; Toshiyuki Takahashi (The Scientific World Journal)
The purpose of this study was to determine any discrepancies in the outputs of five commercial dental radiometers and also to evaluate the accuracy of these devices using a laboratory-grade spectroradiometer. The power densities of 12 different curing light sources were repeatedly measured for a total of five times using each radiometer in a random order. The emission spectra of all of the curing light sources were also measured using the spectroradiometer, and the integral value of each spectrum was calculated to determine the genuine power densities, which were then compared to the displayed power densities measured by the dental radiometers. The displayed values of power density were various and were dependent on the brand of radiometer, and this may be because each radiometer has a different wavelength sensitivity. These results cast doubt upon the accuracy of commercially available dental radiometers.